Festín en el paraíso: Ţiganiada de Ion Budai-Deleanu - Ortega Román, Juan José (Revista de Filología Románica, 2008)
Our purpose is to analyze Ion Budai-Deleanu’s Ţiganiada from a very special point of view regarding the human senses and also to make a particular deconstruction of its space. Earth and Heaven, Hell and Paradise are together out of moral, social and religious prejudices in order to offer us the pagan world of the senses.